Symptomatic Rathke's cleft cyst with a co-existing pituitary tumor; Brief review of the literature - Babu, Ranjith; Back, Adam; Komisarow, Jordan; Owens, Timothy; Cummings, Thomas; Britz, Gavin (Asian Journal of Neurosurgery, 2013)
Pituitary adenomas and Rathke's cleft cysts (RCCs) share a common embryological origin. Occasionally, these two lesions can present within the same patient. We present a case of a 39-year-old male who was found to have a large sellar lesion after complaints of persistent headaches and horizontal nystagmus. Surgical resection revealed components of a RCC co-existing with a pituitary adenoma. A brief review of the literature was performed revealing 38 cases of co-existing Rathke's cleft cysts and pituitary adenomas. Among the cases, the most common symptoms included headache and visual changes. Rathke's cleft cysts and pituitary adenomas are rarely found to co-exist, despite having common embryological origins. We review the existing literature, discuss the common embryology to these two lesions and describe a unique case from our institution of a co-existing Rathke's cleft cyst and pituitary adenoma.
Keywords: Adenoma; development; neoplasm; pituitary; Rathke's cleft cyst; sella; tumor